Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages risk yourself unnecessarily. Many of the best safety devices on machines in Russia have been designed by the very men who use them. This is a very rare phenomenon in this country, but it need not be. The man who designs good safety measures should be honoured as having made an important contribution to production. Hoists, Lifts, Chains and Ropes (Factories Act, Part II, Sect. 22 & 23) Obviously, all tackle of this nature can be extremely dangerous if it is half worn out or if it functions out of complete control. The regulations are directed mainly to seeing that mechanical wear is noted by regular inspection, before it is too late. Further, they are directed to seeing that in dangerous procedures, such as raising or lifting heavy and bulky goods, there is more than one line of defence; everything is not dependent just on one rope or chain. Most of the requirements under the Act are common sense; most intelligent workers could have thought them out. Think them out therefore. How would you safeguard your machine before allowing your wife, or daughter, or brother, or son to run it? Cranes and Lifting Machines (Factories Act, Part II, Sect. 24) In the 1939 Annual Report of the Chief Inspector of Factories, comment is made on the many fatal and non-fatal accidents caused by overhead travelling cranes. Mr Topham, Deputy Chief Inspector, states: "These accidents should not and would not occur if the precautions required by Section 24 of the Act were more consistently observed." This statement is a very serious reflection on some one. The regulations are not complex; maintaining gear, keeping within the limits of safe loading, measures to warn men or women working near the wheel-track, are the main ones; just the precautions that any thoughtful person would take before swinging a ten-ton steel girder through a busy workshop. These are samples of the legal regulations designed to prevent accidents; in the Factories Act there are details of the safety regulations for the provision of fire escapes, treatment of explosive materials and fumes, steam boilers and containers, water-sealed gasholders, and so on, concerning which further details can be found in the Act itself. Weight Lifting There are certain actions that are of themselves conducive to a high accident rate and these require special consideration from this angle. Weight lifting is such an action. Section 56 (1) of the 17 21/2049